Biotechnological approaches for production of bioactive secondary metabolites in Nigella sativa: an up-to-date review - Abeer Kazmi; Mubarak Ali Khan; Huma Ali (International Journal of Secondary Metabolite)
Medicinal and aromatic plants and their refined natural products have gained global attraction for their therapeutic potential against many human diseases. Nigella sativa is a medicinally important plant, commonly known as Black cumin or Black seed is a dicotyledon plant of the Ranunculaceae family. It is in common use for a longer time in history as preservative and spice and has also been extensively utilized by different communities around the globe. Black cumin has been an eminent component of traditional medicine systems like Unani and Tibb, Ayurveda and Siddha. Its biological activities include antidiarrheal, analgesic, antibacterial, liver tonic, diurectic, digestive agent and to treat several skin disorders. Furthermore, the therapeutic properties also include antidiabetic, anticancer, antihypertensive, anti-inflammatory, hepatoprotective, spasmolytic and bronchodialator. This is all because of its miraculous healing power that it has been ranked as top ranked, among evidence based herbal medicines. The literature supports that the pharmacological activities of Nigella sativa are mainly because of the essential oil and its constituents particularly thymoquinone. The current review is an attempt to present a detailed literature survey regarding chemical composition, phytochemistry, therapeutic potential and biotechnological approaches to enhance the medicinal potential of this valuable plant.